Financial literacy and retirement planning in Finland - Kalmi, Panu; Ruuskanen, Olli-Pekka (Cambridge University Press, 2018)
This paper presents the results from the first study of financial literacy in Finland and explores the relationship between financial literacy and retirement planning in Finland. Finland is an interesting case because countervailing effects may exist: a high level of education might increase financial literacy, while the high provision of social security may decrease it and weaken its relationship with pension planning. The results indicate that the level of financial literacy in Finland is comparatively high, although it is unequally distributed among the population. With respect to pension planning, we find that there is little evidence of a relationship between the three core financial literacy questions and retirement planning; however, a statistically significant and positive relationship exists between retirement planning and an extended measure of financial literacy, consisting mostly of more demanding questions. When we split the sample by gender, we find evidence of a positive relationship between financial literacy and retirement planning among women but not among men. The results indicate that scaling down publicly guaranteed pension benefits may pose a challenge to the less financially literate segment of the population.
Keywords: fi=Taloustiede|en=Economics|